Unplanned Urban Expansion and Natural Sensitivity in Chhorepatan, Pokhara - Poudel, Khagendra Raj; Paudel, Naresh (The Third Pole: Journal of Geography Education, 2024)
Chhorepatan, one of the geologically sensitive tourist hubs in Pokhara Valley, has undergone rapid and unplanned urbanization in the last five decades, changing its topography significantly. This research paper explores the unplanned urban expansion and natural sensitivities in Chhorepatan, Pokhara Metropolitan City. This paper uses satellite data, field surveys, and historical data to assess the impact of urban expansion on the area's geologically sensitive landscape using RS, GIS tools. The finding based on the satellite images of 1990-2020 reveals that rapid expansion of built-up sensitive areas increases subsidence risks, particularly in sinkhole and cave zones. Urban growth of Chhorepatan area, exacerbated by population growth and infrastructure development over the geologial sensitive area, poses a significant threat to environmental stability and human life. It is suggested that the policy should incorporate geological assessments into urban planning for sustainable development and disaster reduction in geologically sensitive regions.